2016
DOI: 10.1210/en.2016-1411
|View full text |Cite
|
Sign up to set email alerts
|

Excess Testosterone Exposure Alters Hypothalamic-Pituitary-Testicular Axis Dynamics and Gene Expression in Sheep Fetuses

Abstract: Prenatal exposure to excess androgen may result in impaired adult fertility in a variety of mammalian species. However, little is known about what feedback mechanisms regulate gonadotropin secretion during early gestation and how they respond to excess T exposure. The objective of this study was to determine the effect of exogenous exposure to T on key genes that regulate gonadotropin and GnRH secretion in fetal male lambs as compared with female cohorts. We found that biweekly maternal testosterone propionate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…Recent studies have shown that exposing developing male lamb fetuses to excess androgen prior to midgestation inhibits pituitary gonadotropin secretion and suppresses expression of testicular enzymes catalyzing T production. Using the same treatment paradigm as the current study, we found previously that excess T suppressed LH levels and androgen synthesis enzyme expression in the testis as early as day 60 of gestation [12]. This effect was reversed two weeks after treatment stopped suggesting that the testicular disruption was shortlived.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Recent studies have shown that exposing developing male lamb fetuses to excess androgen prior to midgestation inhibits pituitary gonadotropin secretion and suppresses expression of testicular enzymes catalyzing T production. Using the same treatment paradigm as the current study, we found previously that excess T suppressed LH levels and androgen synthesis enzyme expression in the testis as early as day 60 of gestation [12]. This effect was reversed two weeks after treatment stopped suggesting that the testicular disruption was shortlived.…”
Section: Discussionsupporting
confidence: 61%
“…USA) following the manufacturer's instructions. RNA sample concentration and purity were evaluated as described previously [12]. RNA was reverse transcribed to cDNA using Oligo dT primers with the First Strand Superscript III Kit (Invitrogen, Carlsbad, CA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings highlight the exquisite sensitivity of the developing female brain, which ordinarily is exposed to very low androgens during development, and suggest that the male brain, which in late gestation is exposed to elevated gonadal testosterone, is able to compensate. The male reproductive axis is functional before birth in male foetuses, and maintains homeostatic levels of serum testosterone via negative feedback mechanisms 12,57,58 . Therefore, it is plausible that in males the active hypothalamic-pituitary-testicular axis is able to compensate for exogenous androgen exposure during prenatal development by adjusting LH secretion from the anterior pituitary and downstream testosterone synthesis to consequently restore homeostasis to the androgen milieu in utero .…”
Section: Discussionmentioning
confidence: 99%